Understanding factors associated with delay in seeking treatment among locally advanced and metastatic breast cancer in Hospital Raja Perempuan Zainab II - Karim, Mohd Firdaus A. (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2020)
Breast cancer is the second most cancer common detected in the world, as reported by GLOBOCAN in 2012 and contribute about 25% of overall cancer worldwide.1 It is expected to increase every year as a lot of promotion had been done to increase breast cancer awareness. Despite the public awareness and education regarding breast cancer, patient with locally advanced breast cancer or metastatic breast cancer is still commonly seen in our community. In Kelantan, it had been reported by Cancer Registry 2006, up to 34.9% cases presented at stage 4, comparing only 20.7% in stage 3 and 19% in stage 1.2 Breast cancer is a disease that have good survival rate if detected early as delay in seeking treatment associated with larger tumor, more advanced stage and subsequently poorer prospect of survival. Breast cancer delay can be defined as more than 12 weeks between discovery of the symptom by patient and the beginning of the definitive treatment. This can be further classified as patient delay (waiting 3 months or more before seeking treatment) or health provider delay (one month or more from first patient presentation till beginning of treatment). MA Richard et all had analyzed 2964 patient with different stage of breast cancer, shown that the survival after 10 years for patient presented less than 12 weeks after first symptom was 52% and 47% for longer delays.3 According to The Clinical Practice Guidelines (CPG) on management of breast cancer in Malaysia, it is recommended that breast cancer patient should receive primary treatment within 2 months of presenting symptom.4 The aim of this study is to understand the factors associated with delay in seeking treatment for patient presented with locally advanced and metastatic breast cancer in HRPZ II.